Combustion characteristics of diesel engine using producer gas and blends of Jatropha methyl ester with diesel in mixed fuel mode - Hifjur Raheman; Debasish Padhee (International Journal of Renewable Energy Development, 2014)
An experimental investigation was performed to study the combustion characteristics of diesel engine fuelled with producer gas-biodiesel in dual fuel mode. Three different fuel blends of Jatropha methyl ester with high speed diesel (HSD) (B10, B20) and B100 were used with producer gas obtained from the gasification of briquettes made from de-oiled Jatropha seed cake. The increments in load on the engine increased the brake thermal efficiency, exhaust gas temperature and lowered the brake specific energy consumption. The ignition delays in dual-fuel mode of operation for both the fuels were longer than for single-fuel mode of operation. Combustion pressure and heat release rate (HRR) patterns at different engine loads were found to be similar for biodiesel and HSD. In dual-fuel mode, the peak pressure and HRR for producer gas–biodiesel dual-fuel were slightly lower than those of producer gas–diesel combustion at full load condition. Significantly lower NOx emissions were obtained under the dual fuel mode of operation for both pilot fuels compared to the single-fuel mode especially HSD under all test conditions.